2018
DOI: 10.1007/s10096-018-3221-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different peritoneal dialysis fluids on the in vitro activity of fosfomycin against Escherichia coli, Staphylococcus aureus, Staphylococcus epidermidis, and Pseudomonas aeruginosa

Abstract: Peritonitis is still the main infectious complication among patients on peritoneal dialysis. For treatment of peritoneal dialysis-related peritonitis, the intraperitoneal administration of antibiotics admixed to peritoneal dialysis fluids (PDFs) should be preferred. However, the influence of diverse PDFs on the activity of frequently used antibiotics has been investigated insufficiently. Thus, the present study set out to investigate the in vitro activity of fosfomycin against Escherichia coli, Pseudomonas aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…Decreased antimicrobial activity of aztreonam in vitro, in glucose containing Physioneal, could be explained due reduced growth of P. aerigunosa in this PDF. This phenomenon was already explained in our previous studies 16 . These findings are in parts compatible to an older study by Fuiano et al who reported the effectiveness of aztreonam in combination with cefuroxime for the therapy of PD-associated peritonitis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Decreased antimicrobial activity of aztreonam in vitro, in glucose containing Physioneal, could be explained due reduced growth of P. aerigunosa in this PDF. This phenomenon was already explained in our previous studies 16 . These findings are in parts compatible to an older study by Fuiano et al who reported the effectiveness of aztreonam in combination with cefuroxime for the therapy of PD-associated peritonitis.…”
Section: Discussionsupporting
confidence: 82%
“…Time-kill curves with P. aeruginosa ATCC 27853 were performed in Physioneal with 2.27% glucose, Nutrineal, Extraneal, and in cation-adjusted Mueller Hinton broth (CA-MHB) as comparator fluid 15 . Bacteria were grown overnight on 5% sheep blood agar plates at 37 °C, suspended in 0.9% sterile saline to a concentration equivalent to a 0.5 McFarland standard, and diluted 1:100 in PDFs or CA-MHB to obtain final inoculums 16 . Aztreonam was added in PDFs and CA-MHB to achieve final concentration of 20 µg/ml (5 × MIC) and incubation followed on an orbital shaker for 24 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…This has been confirmed in a randomised controlled trial comparing once-daily gentamicin dose versus continuous dosing; treatment success and relapse rate did not differ between the two regimens. The once-daily dosing strategy, nevertheless, was associated with lower trough 197,198,199 , MD 20 mg/L 197,200 Fosfomycin 4 g daily 201,202 No data Imipenem/cilastatin 500 mg in alternate exchange 203 LD 250 mg/L, MD 50 mg/L LD: loading dose in mg; MD: maintenance dose in mg; IP: intraperitoneal; APD: automated peritoneal dialysis. a IP ampicillin is not recommended for treatment of enterococcal peritonitis.…”
Section: Dosage Of Antibioticsmentioning
confidence: 99%
“…Penicilline G Amoxicilline Ampicilline a Ampicillin/ sulbactam Piperacilline/ tazobactam Ticarcilline/acide clavulanic Pas d'information Pas d'information 4 gm/jour [185] Pas d'information Pas d'information LD 50,000 unit/L, MD 25000unit/L [13] MD 150 mg/L [184] MD 125 mg/L [186] LD 1000 mg/500 mg, MD 133.3 mg/66.7 Mg [187,188] LD 4 gm/0.5 gm, MD 1 gm/0.125 gm [189] LD 3 gm/0.2 gm, MD 300 mg/20 mg/L [190] Autres Aztreonam Ciprofloxacine Clindamycine Daptomycine Fosfomycine Imipenem/cilastatine Ofloxacine Polymyxine B Quinupristine/ dalfopristine Méropénem Teicoplanine Vancomycine 2 gm/jour [191] Pas d'information Pas d'information 300 mg jour [196] 4 g jour [201,202] 500 mg une poche sur deux [203] Pas d'information Pas d'information 25 mg/L une poche sur deux b [205] 500 mg/jour (pour échange long en DPA) [207] 1000 mg/jour (pour échange court en DPCA) [208,209) 15 mg/kg tous les 5 jours [210] 15-30 mg/kg tous les 5-7 jours c [141,212] en DPCA, 15 mg/kg tous les 4 j [213] en DPA LD 500 mg/L192, MD 250 mg/L [192,193] MD 50 mg/L [194] MD 600 mg/poche [195] LD 100 mg/L [197,198,199], MD 20 mg/L [197,200] Pas d'information LD 250 mg/L, MD 50 mg/L [182] LD 200 mg, MD 25 mg/L [204] MD 300,000 unités (30 mg)/poche [188] Pas d'information MD 125 mg/L [206] LD 400 mg/poche, MD 20 mg/L [211,140] LD 20-25 mg/kg, MD 25 mg/L…”
Section: Pénicillinesunclassified